Advantages and Disadvantages of Using Magnetic Nanoparticles for the Treatment of Complicated Ocular Disorders - Elena K. Schneider-Futschik; Felisa Reyes-Ortega (MDPI AG, 2021)
Nanomaterials provide enormous opportunities to overcome the limitations of conventional ocular delivery systems, such as low therapeutic efficacy, side effects due to the systemic exposure, or invasive surgery. Apart from the more common ocular disorders, there are some genetic diseases, such as cystic fibrosis, that develop ocular disorders as secondary effects as long as the disease progresses. These patients are more difficult to be pharmacologically treated using conventional drug routes (topically, systemic), since specific pharmacological formulations can be incompatible, display increased toxicity, or their therapeutic efficacy decreases with the administration of different kind of chemical molecules. Magnetic nanoparticles can be used as potent drug carriers and magnetic hyperthermia agents due to their response to an external magnetic field. Drugs can be concentrated in the target point, limiting the damage to other tissues. The other advantage of these magnetic nanoparticles is that they can act as magnetic resonance imaging agents, allowing the detection of the exact location of the disease. However, there are some drawbacks related to their use in drug delivery, such as the limitation to maintain efficacy in the target organ once the magnetic field is removed from outside. Another disadvantage is the difficulty in maintaining the therapeutic action in three dimensions inside the human body. This review summarizes all the application possibilities related to magnetic nanoparticles in ocular diseases.